Alternative pathway of metronidazole activation in Trichomonas vaginalis hydrogenosomes - Hrdý, Ivan; Cammack, Richard; Stopka, Pavel; Kulda, Jaroslav; Tachezy, Jan (Antimicrobial agents and chemotherapy, 2005)
Metronidazole and related 5-nitroimidazoles are the only available drugs in the treatment of human urogenital trichomoniasis caused by the protozoan parasite Trichomonas vaginalis. The drugs are activated to cytotoxic anion radicals by their reduction within the hydrogenosomes. It has been established that electrons required for metronidazole activation are released from pyruvate by the activity of pyruvate:ferredoxin oxidoreductase and transferred to the drug by a low-redox-potential carrier, ferredoxin. Here we describe a novel pathway involved in the drug activation within the hydrogenosome. The source of electrons is malate, another major hydrogenosomal substrate, which is oxidatively decarboxylated to pyruvate and CO2 by NAD-dependent malic enzyme. The electrons released during this reaction are transferred from NADH to ferredoxin by NADH dehydrogenase homologous to the catalytic module of mitochondrial complex I, which uses ferredoxin as electron acceptor. Trichomonads acquire high-level metronidazole resistance only after both pyruvate- and malate-dependent pathways of metronidazole activation are eliminated from the hydrogenosomes.
Keywords: financování organizované; Trichomonas vaginalis; léková rezistence; Animals; Financing, Organized; Drug Resistance; antitrichomonádové látky; zvířata; organely; Organelles; Antitrichomonal Agents; metronidazol; Metronidazole